Some features of plasma bubble induced scintillations during the AICPITS campaigns of 1991 - Vijayakumar, P.N.; Tyagi, T.R.; Singh, Lakha; Chandra, H.; Vyas, G.D.; Rao, D.R.K.; Pathan, B.M.; Iyer, A.; Ramsekaran, B.; Naidu, A.; Sadique, S.M.; Iyer, K.N.; et al. (My University, 2007)
The VHF scintillations were recorded at a chain of low-latitude stations in India as part of the All India Coordinated Programme of Ionospheric and Thermospheric Studies (AICPITS), using the 244 MHz radio beacon from the geo-stationary satellite FLEETSAT which was located at 73° E longitude. Data collected during the second campaign of September-October 1991 and analyzed jointly by the participating investigators are presented. The onset times of scintillation at pairs of stations at similar latitude but different longitudes can be used to estimate the eastward drift of the scintillation patches and its E-W extent. The maximum monthly mean occurrence for September 1991 is about 35% at Trivandrum and Tiruchendur, the stations close to dip equator. Occurrence is maximum for stations Annamalainagar, Payyanur and Anantpur (50 %), located slightly north of the dip equator. It decreases further north to 30 % at Nuzvid, Bombay, 20 % near anomaly crest region, 10 % at Agra and 8 % at Delhi, which is the northern most edge of the present observations. The occurrence frequency is slightly less than that observed during the campaign of March 1991. For the sake of completeness some very interesting features and dynamical characteristics of plasma bubble induced scintillations are included here based on digital records of scintillations made at Delhi during the two equinox data campaigns in March-April 1991 and September-October 1991.
Keywords: Plasma bubbles; VHF scintillations; Equinox data campaigns; AICPITS